GENOTYPE - ASSOCIATED PERSONIFICATION OF DIAGNOSTIC SEARCH FOR OBESITY IN CHILDREN WITH GENOTYPES OF LACTASE GENE - Abaturov О.E.; Nikulina A.О.; Krivusha О.L.; Aleynikova Т.D. (World of Medicine and Biology, 2018)
Obesity in children is a global problem due not only to the prevalence of this pathology, but also to low detectability. Objective: to study clinical and anamnestic features in obesity in children with different genotypes of the lactase gene. Materials and methods. Based on the results of genotyping of the lactase gene by polymerase chain reaction from 86 obese children aged 6-18 years, observation groups were formed: group I (n=44) was presented by children with genotype C/C 13910 associated with lactase insufficiency adult type, group II (n=41) – children with genotypes C/T and T/T 13910, associated with lactase persistence. The study of violations of fat metabolism was carried out using the bioimpedanceometry method, an ultrasound method of examining internal organs. Results of the study. In mothers of children with genotype C/C 13910, gestational diabetes is significantly more likely to be registered (relative risk (RR)=2.13, diagnostic coefficient (DC) = 3.27, p=0.008). Children with genotype C/C 13910 significantly higher levels of protein-energy deficiency in early childhood (RR=2.39; DK=3.79; p=0.014). In the group of children with genotype C/C 13910, the level of registration of extreme obesity of the 3rd class according to the abdominal type (in 25%, against the comparison group in 7.3% of cases), arterial hypertension (in 27.3%, against the comparison group - in 9.8% of cases), acantosis nigricans (in 20%, against 10% of children with genotype C/T 13910 and 0% of children with genotype T/T 13910) and acne vulgaris (in 34.1%, against the comparison group in 9.5% of cases). When sonographic examination of internal organs in children with genotype C/C 13910, indirect signs of steatohepatosis (in 34.1%, against the comparison group in 17.6% of cases) are significantly more likely to be recorded. Conclusions. Formation of anamnestic triggers and clinical symptoms of insulin resistance in obesity in children 6 -18 years old has genotype-associated character. The most unfavorable from the point of view of the metabolic prognosis of type 2 diabetes and cardiovascular risk is the genotype С/C 13910. Mothers of children with genotype C / S 13910 reliably register gestational diabetes. In children with genotype C / C 13910 at birth and in the first year of life, the level of protein-energy insufficiency of various degrees of severity is significantly higher, which coincides with the theory of "economical genotype", which considers a small mass at birth and in early childhood as a trigger factor of insulin resistance. In the group of children with genotype C / S 13910, the level of registration of extreme obesity by abdominal type, arterial hypertension, acantosis nigricans and acne vulgaris is significantly higher. In the sonographic examination of the abdominal organs, in children with genotype C / S 13910, indirect signs of steatohepatosis are significantly more frequently recorded. Dissociation of puberty in children with genotype C / C 13910 is characterized by premature sexual development in girls and delayed sexual development of boys within 1-2 years by the Tanner classification, which correlates with more frequent clinical manifestations of insulin resistance in this genotype.